2021
DOI: 10.4103/aip.aip_95_20
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Burden and Psychiatric Morbidity Among Caregivers of Children with Thalassemia Major

Abstract: Background: Caregivers of children with thalassemia major experience higher caregiver burden and psychiatric morbidity. Aims: The aims of this study were as follows: (1) to assess the caregiver burden and psychiatric morbidity among caregivers of children with thalassemia major and (2) correlation between caregiver burden and psychiatric morbidity. Settings and Design: This was an observational, cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
0
1
Order By: Relevance
“…Study performed by Abbasi & Manzoor [27], whose conduct study in Pakistan (study sample equal 200 caregivers) and entitled as " Socio-religious prognosticators of psychosocial burden of beta thalassemia major" who stated that, there was significant relation between caregivers' total burnout score and their demographic data as age, gender, marital status, place of residence and income. Also, these results disagreed with study performed by Prajapati et al [24], who found that, there was no relation between age, gender, place or residence, education, occupation and marital status. From the researcher point of view, these results might be due to those families who residing in urban areas, sufficient income , higher education and employed had better opportunity to acquire more knowledge regarding thalassemia, They own recreational places in cities such as clubs and parks, places of health care are close to them, so they do not have to tire or waste time in transportation, they form relationships and friendship with others because of the nature of their jobs and that relieves the degree of burnoutRegarding to Correlation between caregivers` total knowledge and total burnout regarding thalassemia of their children, the results of the current study showed that, there were highly statistically significant positive correlation between total knowledge scores of caregivers and total caregiver`s burnout (p= 0.000**).These results agreed with study performed by Abbasi & Manzoor [27],whose conduct study in Pakistan (study sample equal 197 perants) and entitled as "Socio-religious prognosticators of psychosocial burden of beta thalassemia major" who found that, there were positive correlation between total knowledge scores of caregivers and total caregiver`s burnout.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Study performed by Abbasi & Manzoor [27], whose conduct study in Pakistan (study sample equal 200 caregivers) and entitled as " Socio-religious prognosticators of psychosocial burden of beta thalassemia major" who stated that, there was significant relation between caregivers' total burnout score and their demographic data as age, gender, marital status, place of residence and income. Also, these results disagreed with study performed by Prajapati et al [24], who found that, there was no relation between age, gender, place or residence, education, occupation and marital status. From the researcher point of view, these results might be due to those families who residing in urban areas, sufficient income , higher education and employed had better opportunity to acquire more knowledge regarding thalassemia, They own recreational places in cities such as clubs and parks, places of health care are close to them, so they do not have to tire or waste time in transportation, they form relationships and friendship with others because of the nature of their jobs and that relieves the degree of burnoutRegarding to Correlation between caregivers` total knowledge and total burnout regarding thalassemia of their children, the results of the current study showed that, there were highly statistically significant positive correlation between total knowledge scores of caregivers and total caregiver`s burnout (p= 0.000**).These results agreed with study performed by Abbasi & Manzoor [27],whose conduct study in Pakistan (study sample equal 197 perants) and entitled as "Socio-religious prognosticators of psychosocial burden of beta thalassemia major" who found that, there were positive correlation between total knowledge scores of caregivers and total caregiver`s burnout.…”
Section: Discussioncontrasting
confidence: 94%
“…Regarding to total burnout of the studied caregiver, the results of the current study showed that, less than three quarters of studied caregivers had high burnout and less than one third had low burnout. These results agreed with study performed by Prajapati et al [24], who found that, 69% of studied caregivers had high burnout. From the researcher point of view, these results might be due to insufficient social support from relative, neighbors and insufficient financial support from community.…”
Section: Discussionsupporting
confidence: 93%